Bullying and giftedness in school environment - Rondini, Carina Alexandra [UNESP] (2021)
Bullying is characterized by constant violent actions against the same individual. Bullied people suffer physical and psychological damage that directly affect their academic achievement, as well as their relationship with friends, family, and society, resulting in a feeling of social exclusion. Based on the hypothesis that myths and prejudices about giftedness contribute for gifted students to be involved with bullying, we propose an exploratory study of bullying experienced by gifted students in school environments. Interviews were carried out with a non-probabilistic sample composed of ten gifted students of Middle School. Our investigation states that some characteristics of giftedness can help them to deal better with bullying consequences and have an interventionist attitude in a situation of bullying. Moreover, the areas of giftedness can influence how these students use aggression when assuming the role of bullies. At last, it is identified that the myths of giftedness did not lead to their involvement with bullying.